Contribution of the Integrated Batik Learning Model of the Leadership Project in Improving the Competency of PPG Arts and Culture Students - Ratnawati, Ike; Wardhana, Mitra Istiar; Habiddin, Habiddin; Conseta, Maria Goretti Indah Della; Muslim, Muslim; Suryantoro, Ira Junita (Journal of English Language and Education, 2025)
This study aims to examine the contribution of the integrated batik learning model of leadership projects to the competency development of students in the Teacher Professional Education Program (PPG) for Cultural Arts within the implementation of the Independent Curriculum. This model is designed to cultivate students' practical skills in managing art projects while embedding leadership within a cultural context. Employing a case study method with a qualitative approach, data were collected through interviews, observations, and document analysis. The findings indicate that integrating batik learning with leadership projects enhances students’ creativity, collaboration, and ability to manage artistic productions. Additionally, students demonstrate significant improvements in leadership capabilities, particularly in organizing and managing art-related projects. This learning model aligns with the core principles of the Independent Curriculum, which emphasize a project-based approach and character development. The study recommends further development to broaden the implementation of this model in the field of cultural arts education.